Asociation between nutritional status and depressive symptoms in a Peruvian adult population: A population-based study in Peru - Escalante-Ramírez, Daniel (2022)
Introduction. Among the Peruvian population, the prevalence of overweight and obesity has increased, making it one of the main public health problems. There is also conflicting evidence on the association between increased BMI and depressive symptoms in the adult population. Objective. To determine the association between nutritional status (NS) and depressive symptoms (DS) in the Peruvian population. Method. We conducted a secondary data analysis of the Peruvian Demographic and Family Health Survey (ENDES). We assessed the NS according to body mass index (BMI), grouped into normal weight (BMI = 18.50 - 24.99), overweight (BMI = 25.00 - 29.99), 1A obesity (BMI = 30.00 - 32.49), and 1B obesity (BMI ≥ 32.50). DS were assessed using the Patient Health Questionnaire (PHQ-9) instrument. A generalized linear model stratified by sex was constructed to calculate crude (cPRc) and adjusted (aPR) prevalence ratios. Results. A total of 26,463 records of people aged 18-60 years were assessed, yielding a 6.3% prevalence of DS (≥ 10 points). Females had a higher frequency of DS than males, which increased depending on their NS: normal weight 7.8%, overweight 8.2%, 1A obesity 9.0%, and 1B obesity 12.0%. Likewise, in the multivariate analysis, women with 1B obesity reported a higher frequency of DS (aPR = 1.30; 95% CI = [1.03, 1.63]). Discussion and conclusion. There is a strong association between nutritional status and depressive symptoms in Peruvian women, with obese women being more likely to have depressive symptoms.